Since `-8` does not contain the variable to solve for, move it to the right-hand side of the equation by adding `8` to both sides. `8r=8-32` Subtract `32` from `8` to get `-24` . `8r=-24` Divide each term in the equation by `8` . `(8r)/(8) =-24/8` Simplify the left-hand side...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Since `-8` does not contain the variable to solve for, move it to the right-hand side of the equation by adding `8` to both sides.

`8r=8-32`

Subtract `32` from `8` to get `-24` .

`8r=-24`

Divide each term in the equation by `8` .

`(8r)/(8) =-24/8`

Simplify the left-hand side of the equation by canceling the common factors.

`r = -24/8`

Simplify the equation. Therefore,

`r = -3`

Solve `8r - 8 =-32.`

Add 8 to both sides to combine like terms.

`8r-8+8 = -32+8`

`8r = -24` Divide both sides by 8.

`(8r)/8 = (-24)/8`

`r = -3`

**The solution is r = -3.**